2017
DOI: 10.1007/s00401-017-1762-2
|View full text |Cite
|
Sign up to set email alerts
|

MSA prions exhibit remarkable stability and resistance to inactivation

Abstract: Acknowledgments: We thank the Hunters Point animal facility staff for breeding and caring for the mice used in this study and Martin Ingelsson (Uppsala University) for providing control tissue. This work was supported by grants from the National Institutes of Health (AG002132 and AG031220), as well as by gifts from the Glenn Foundation and Daiichi Sankyo. The resulting from prion adherence to surgical steel instruments, has been investigated by incubating steel sutures in contaminated brain homogenate before i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 55 publications
7
65
0
Order By: Relevance
“…Indeed, these results can be replicated by inoculating homogenate from the first transplanted rat brain into a second rat brain (Prusiner et al, 2015). Similar results can be found when the rat is exposed peripherally (like peritoneal cavity) to the homogenates of MSA brains (Woerman et al, 2018). Nevertheless, some issues need to be taken into account, like the fact that these results could not be obtained in wild-type (WT) mice (Prusiner et al, 2015).…”
Section: Prion-like Characteristics Of α-Synsupporting
confidence: 52%
“…Indeed, these results can be replicated by inoculating homogenate from the first transplanted rat brain into a second rat brain (Prusiner et al, 2015). Similar results can be found when the rat is exposed peripherally (like peritoneal cavity) to the homogenates of MSA brains (Woerman et al, 2018). Nevertheless, some issues need to be taken into account, like the fact that these results could not be obtained in wild-type (WT) mice (Prusiner et al, 2015).…”
Section: Prion-like Characteristics Of α-Synsupporting
confidence: 52%
“…In PD, PDD, and DLB patients, α-synuclein accumulates in neurons as Lewy bodies and Lewy neurites (2). Recent studies demonstrate that MSA is unequivocally caused by α-synuclein prions, which are misfolded proteins that undergo self-propagation and are capable of transmitting disease to transgenic (Tg) mice (3)(4)(5)(6). Using TgM83 +/− mice, which express human α-synuclein with the familial A53T mutation, both intracranial (3,5) and peripheral inoculation (6) of brain homogenate from a total of 17 MSA patients induced neurological disease in the animals.…”
mentioning
confidence: 99%
“…Moreover, recent experiments in cell and animal models use preformed SYN fibrils or brain homogenates from human LBD subjects to induce spread of SYN pathology that results in neuron loss and dysfunction as well as motor phenotypes which further supports this theory. Most recently, separate SYN species have been identified that may have different “strain‐like” properties, with certain preparations being additionally capable of cross‐seeding either tau or Aβ and others leading to MSA‐type pathologies . However, the core prion feature of infectivity has not clearly been demonstrated for LBD or AD in humans …”
Section: The Role Of Alpha‐synuclein In Lbd Pathogenesismentioning
confidence: 99%
“…Most recently, separate SYN species have been identified that may have different "strain-like" properties, with certain preparations being additionally capable of crossseeding either tau [54][55][56] or Aβ 57 and others leading to MSAtype pathologies. [58][59][60] However, the core prion feature of infectivity has not clearly been demonstrated for LBD or AD in humans. 61 Many autopsy studies have shown a correlation of LP with motor disease severity in PD.…”
Section: The Role Of Alpha-synuclein In Lbd Pathogenesismentioning
confidence: 99%